Oxidative stress induced by UVA photoactivation of the tryptophan UVB photoproduct 6-formylindolo[3,2-b]carbazole (FICZ) inhibits nucleotide excision repair in human cells - Brem, Reto (Sci Rep, 2017)
Potentially mutagenic DNA lesions induced by UVB (wavelengths 280–320 nm) are important risk factors for solar ultraviolet (UV) radiation-induced skin cancer. The carcinogenicity of the more abundant UVA (320–400 nm) is less well understood but is generally regarded to reflect its interaction with cellular chromophores that act as photosensitisers. The arylhydrocarbon receptor agonist 6-formylindolo[3,2-b] carbazole (FICZ), is a UVB photoproduct of tryptophan and a powerful UVA chromophore. Combined with UVA, FICZ generates reactive oxygen species (ROS) and induces oxidative DNA damage. Here we demonstrate that ROS generated by FICZ/UVA combinations also cause extensive protein damage in HaCaT human keratinocytes. We show that FICZ/UVA-induced oxidation significantly inhibits the removal of potentially mutagenic UVB-induced DNA photolesions by nucleotide excision repair (NER). DNA repair inhibition is due to FICZ/UVA-induced oxidation damage to the NER proteome and DNA excision repair is impaired in extracts prepared from FICZ/UVA-treated cells. NER protects against skin cancer. As a likely UVB photoproduct of intracellular tryptophan, FICZ represents a de facto endogenous UVA photosensitiser in sun-exposed skin. FICZ formation may increase the risk of solar UV-induced skin cancer by promoting photochemical damage to the NER proteome and thereby preventing the removal of UVB-induced DNA lesions.